Global Robust Exponential Stability Analysis for Interval Neural Networks with Mixed Delays. (18th December 2012) - Du, Yanke; Xu, Rui
Abstract : A class of interval neural networks with time-varying delays and distributed delays is investigated. By employing H -matrix and M -matrix theory, homeomorphism techniques, Lyapunov functional method, and linear matrix inequality approach, sufficient conditions for the existence, uniqueness, and global robust exponential stability of the equilibrium point to the neural networks are established and some previously published results are improved and generalized. Finally, some numerical examples are given to illustrate the effectiveness of the theoretical results.